Project Management and Engineering Research AEIPRO 2017 - Ayuso Muñoz, José Luis; Yagüe Blanco, José Luis; Capuz-Rizo, Salvador F. (Lecture Notes in Management and Industrial Engineering, 2019)
This is the Proceedings of the 20th International Congress on Project Management and Engineering, that was held at the Technical University of Cartagena, Spain, from July 13 to 15, 2016. It brings together a collection of recent works of researchers and professionals in the Project Management and Engineering fields of Civil Engineering and Urban Planning, Product and Process Engineering, Environmental Engineering, Energy Efficiency and Renewable Energies and Safety, Labour Risks and Ergonomics. .